Evaluating the use of plerixafor in stem cell mobilisation – an economic analysis of the PHANTASTIC trial. Issue 5 (29th September 2015) - Martin, Antony P.; Richards, Sarah; Haycox, Alan; Houten, Rachel; McLeod, Claire; Braithwaite, Barbara; Clark, Jack O.; Bell, Joanne; Clark, Richard E.
Abstract : Plerixafor is an effective haematopoietic stem cell mobilising agent in candidates for autologous transplantation, including patients with myeloma and lymphoma. Here we compare 98 plerixafor recipients in the PHANTASTIC trial with 151 historic controls mobilised by conventional chemotherapy (each with granulocyte colony‐stimulating factor, G‐CSF). Seventy (71.4%) plerixafor‐mobilised patients achieved the composite primary endpoint of ≥4 × 10 6 CD34+ cells kg −1 in ≤2 aphereses and no clinically significant neutropenia, compared to 48 (31.8%) historic controls ( P < 0.001), and this significant advantage was maintained in scenario analyses testing components of this composite endpoint. A patient‐level cost analysis was undertaken for 249 patients, which included the cost of remobilising patients where initial mobilisation had failed. Combined mean treatment cost for plerixafor mobilised patients was £12, 679 compared with £11, 694 for historical controls. However, plerixafor produces an average saving of £3, 828 per lymphoma patient but average cost increase by £5, 245 per myeloma patient. The present data demonstrate cost‐effectiveness for plerixafor as a first line mobilisation agent, certainly for lymphoma patients, where substantial resource savings and achievement of the primary endpoint are likely. J. Clin. Apheresis 31:434–442, 2016. © 2015 Wiley Periodicals, Inc.